A NEW SPECIES OF MURRAYA FROM CYCLOPS MOUNTAIN, PAPUA, INDONESIA - ASTUTI, INGGIT PUJI; RUGAYAH, RUGAYAH (Research Center for Biology, 2016)
ASTUTI, I. P. & RUGAYAH. 2016. A new species of Murraya from Cyclops Mountain, Papua, Indonesia. Reinwardtia 15(2): 111 â114. â A living collection of Bogor Botanic Gardens, planted in plot XXIV.A.192-192a and originated from Kemiri Said Nature Reserve, Cyclops Mountain in Papua collected by Lugrayasa (LG 1352), is described and illustrated as a new species, namely Murraya cyclopensis Astuti & Rugayah. The species is closely related to Murraya paniculata (L.) Jack, in vegetative and flower structures, but differ in the presence of indumentum on twig, rachis and petiole, smaller size of flowers, red globose fruits, and orbicular seeds covered by densely short hairs and red aril.